Vous êtes sur la page 1sur 32

# Year 9 :: Sequences II

Dr J Frost (jfrost@tiffin.kingston.sch.uk)
www.drfrostmaths.com

Teacher Guidance
Possible lesson structure:

## Lesson 1: Linear Sequences Recap and generating sequences Go >

from formulae
Lesson 2: Term-to-term vs Position-to-term and Geometric Sequences Go >
Lesson 3: Quadratic Sequences Go >
Lesson 4: Levelled Sequences Activity

## Lesson 5 : Sequence Proofs Go >

(Teacher pet peeve: I strongly advise against teaching ‘0th term’ to identify the
constant in linear sequences – it generalises poorly to other types of sequence, and
avoids students understanding what the 𝑘𝑛 term in their formula is actually doing)
RECAP: Linear Sequences

## 4, 9, 14, 19, 24, 29, …

The coefficient of 𝑛 is
the difference between
𝑛th term of sequence the numbers.

𝑢𝑛 = 5𝑛
? −? 1
𝑛 means the position
in the sequence, so for
the first term, 𝑛 = 1.
The idea of ‘adjusting’ an initial formula

𝑛 1 2 3 4 5
𝑢𝑛 2 5 8 11 14 …
How would we start
3𝑛
? 3 6 9 ? 12 15 the formula?

## We’re basically using an approach of starting

Therefore formula: the formula with something sensible (here
3𝑛), seeing what sequence this would give
𝑢𝑛 = 𝟑𝒏 −?𝟏 us, and ‘adjusting’ appropriately. For linear
sequences a full written method like this is
slight overkill, but this is what should be
Quickfire Examples
Find formulae for the 𝑛th term of each of these sequences:

## 6, 11, 16, 21, 26, … 𝑢𝑛 = 5𝑛 +?1

9, 7, 5, 3, 1, −1, … 𝑢𝑛 = 11 −?2𝑛

## 12, 9, 6, 3, 0, −3, … 𝑢𝑛 = 15 −?3𝑛

Terminology
 A linear sequence (or ‘arithmetic sequence’) is one where the
difference between terms is constant. 𝑢𝑛 = 𝑎𝑛 + 𝑏
 𝑢𝑛 means the 𝑛th term in the sequence.
(often 𝑎𝑛 or 𝑥𝑛 )

## If we’re currently considering the

𝑛th term, how would we refer to the ?
𝑈𝑛−1
term before that?
This is the ‘position’.

𝑛 1 2 3 4 5 6
𝑢𝑛 𝟐 𝟓 𝟖 𝟏𝟏 𝟏𝟒 𝟏𝟕 …
This is the ‘term’.
i.e. The term at the 4th position is 11.
Going the other way
We can see how to find the 𝑛th term formula for a linear sequence. But you were also
previously required to go the other way: generate a sequence from a (potentially non-
linear) formula.

𝑢𝑛 = 7𝑛 − 3
𝟒, 𝟏𝟏, 𝟏𝟖,?𝟐𝟓, 𝟑𝟐, …
𝑢𝑛 = 5𝑛
𝟓, 𝟐𝟓, 𝟏𝟐𝟓,
? 𝟔𝟐𝟓, …

## Broculator Tip: To generate a sequence:

• Press Mode then TABLE.
of n, using the ALPHA key to get X)
𝑢𝑛 = 2𝑛 − 𝑛2 • Press =. Then use 1 for ‘start’ (i.e. your
𝟏, 𝟎, −𝟏, 𝟎,? 𝟕, 𝟐𝟖, … first value of 𝑛), 10 for ‘end’ (i.e. you
want 10 terms) and 1 for ‘step’ (𝑛
increases by 1 each time). Press =.
• To reset, press MODE then ‘COMP’.
Exercise 1
The 3rd term of a linear sequence is 17. The
1 Determine the formula for theth𝑛th term of each 4
45th term is 269. Determine the formula for
sequence. Hence find the 300 term for each sequence
the nth term.
(i.e. 𝑢300 )
𝒖𝒏 = 𝟔𝒏 − 𝟏 ?
3, 8, 13, 18, … ?
𝒖𝒏 = 𝟓𝒏 − 𝟐, 𝒖𝟑𝟎𝟎 = 𝟏𝟒𝟗𝟖
N1 Two sequences have the formulae
5, 7, 9, 11, … ?
𝒖𝒏 = 𝟐𝒏 + 𝟑, 𝒖𝟑𝟎𝟎 = 𝟔𝟎𝟑 𝑎𝑛 = 3𝑛 − 1 and 𝑏𝑛 = 7𝑛 + 2. A new
3, 4, 5, 6, …
5, 12, 19, 26, …
?
𝒖𝒏 = 𝒏 + 𝟐, 𝒖𝟑𝟎𝟎 = 𝟑𝟎𝟐
𝒖𝒏 = 𝟕𝒏 − 𝟐, 𝒖𝟑𝟎𝟎 = 𝟐𝟎𝟗𝟖
sequence with formula 𝑐𝑛 is formed by the
numbers which appear in both 𝑎𝑛 and 𝑏𝑛 .
? Determine 𝑐𝑛 .
2 Find the first five terms of the sequences with the
𝒄𝒏 = 𝟐𝟏𝒏 + 𝟐
Whatever the first number is that coincides, we’ll see it 21
following (non-linear) equations:
?
later because LCM(7,3)=21. Thus we know 𝒄𝒏 = 𝟐𝟏𝒏 + □.

𝑢𝑛 = 𝑛2 + 𝑛 ?
𝟐, 𝟔, 𝟏𝟐, 𝟐𝟎, 𝟑𝟎
It’s then simply a case of identifying which number this is (2).

𝑢𝑛 = 𝑛3 − 𝑛2 ?
𝟎, 𝟒, 𝟏𝟖, 𝟒𝟖, 𝟏𝟎𝟎 N2 Put the sequences in order of the speed/rate
at which they ‘grow’, the slowest growing first,
𝑢𝑛
𝑢𝑛
= 3𝑛
= 𝑛!
?
𝟑, 𝟗, 𝟐𝟕, 𝟖𝟏, 𝟐𝟒𝟑
𝟏, 𝟐, 𝟔, 𝟐𝟒, 𝟏𝟐𝟎 giving a reason for your order. It may help to
? think what happens as 𝑛 increases by 1 each time.
𝑢𝑛 = 𝑛! 𝑢𝑛 = 𝑛2 𝑢𝑛 = 3𝑛
3 Find the formula for the 𝑛th term of the following 𝑢𝑛 = 𝑛
𝑛
𝑢𝑛 = 22 𝑢𝑛 = 𝑛
sequences.
6, 5, 4, 3, 2, … 𝒖𝒏 = 𝟕 − 𝒏 ? 𝑢𝑛 = 1
1 is the slowest as it does not grow at all (1, 1, 1, 1, …). 𝒏 is next as the square root
causes the sequence to gradually grow slower over time. 𝒏 grows by 1 each time.𝒏𝟐
5, 2, −1, −4, …
1 1
𝒖𝒏 = 𝟖 − 𝟑𝒏
𝟓
? grows by 2𝑛 + 1 each time (as 𝑛 + 1 2 = 𝑛2 + 2𝑛 + 1) which means the difference
increases by a constant amount each time (in this case 2).𝟑𝒏 is next because the numbers
10 , 8, 5 , 3, …
2 2
𝒖𝒏 = 𝟏𝟑 − 𝒏
𝟐? ?
become 3 times larger each time, meaning the difference of the difference increases
unlike 𝑛2.𝒏! is next because the scale factor increases by 1 each time, whereas for 3𝑛 the
1 7 5 1 𝟏 𝟐𝟓 𝒏
2 ,2 ,2 ,3
3 12 6 12
𝒖𝒏 = 𝒏 +
𝟒 ?𝟏𝟐
scale factor is constant (i.e. 3).𝟐𝟐 is last because the scale factor doubles each time,
whereas for 𝑛! it only increased by 1.
Term-to-term and position-to-term formulae

## 1, 4, 7, 10, 13, 16, …

Position-to-term formula
We’ve previous seen how we can use the position 𝑛 to determine the term 𝑢𝑛 .
This is known as a position-to-term formula:

𝑢𝑛 = 3𝑛 − 2
Term-to-term formula
However, we can also get the 𝑛th term of the sequence by thinking of a rule to
get it from the previous term(s)…
Previous term

𝑢𝑛 = 𝑢𝑛−1 + 3
? Why do you think we
𝑢1 = 1 need this?
Starter Investigation
Describe these sequences.

## Formula based on Formula based on position 𝑛

previous terms

𝑢𝑛 = 𝑢𝑛−1 + 2
3, 5, 7, 9, … 𝑢1 = 3 ? 𝑢𝑛 = 2𝑛 + 1 ?
𝑛 𝑛
𝑢𝑛 = 𝑢𝑛−1 + 𝑢𝑛−2 1 1+ 5 1− 5
1, 1, 2, 3, 5, … ?
𝑢1 = 1, 𝑢2 = 1
𝑢𝑛 =
5
Ermm…. ?
2

2

𝑢𝑛 = 2𝑢𝑛−1
2, 4, 8, 16, … 𝑢1 = 2 ? 𝑢𝑛 = 2𝑛 ?

## Bro Tip: This is an exam favourite!

Geometric Sequences
 A geometric sequence is one in which we multiply by a constant each time.
(In contrast to an arithmetic sequence where we add each time)

𝑛 1 2 3 4 5
𝑢𝑛 4 8 16 32 64 …
𝑛 How could we start the
2? 2 4 8 ? 16 32 formula to get this
doubling pattern?

## 𝑢𝑛 = 𝟐 𝟐𝒏 ?= 𝟐𝒏+𝟏 we’re multiplying by 𝑘 each time,

start the formula as 𝑘 𝑛 .
Another Example

𝑛 1 2 3 4 5
𝑢𝑛 2 6 18 54 162 …
𝑛
3
? 3 9 27? 81 243
Adjustment × 2 … ?
3

Therefore formula:
𝟐 𝒏 For geometric sequences where

= 𝟐 𝟑?𝒏−𝟏
we’re multiplying by 𝑘 each time,
𝑢𝑛 = 𝟑? start the formula as 𝑘 𝑛 .
𝟑

𝒏
𝒖𝒏 = 𝟑 𝟏𝟎 ?

## 4, 20, 100, 500, …

𝟒 𝒏
𝒖𝒏 = 𝟓 ? = 𝟒 𝟓𝒏−𝟏
𝟓
Exercise 2
For each of the following determine: 8, 24, 72, 216, 648 …
5
(a) the position-to-term formula and 𝟖
𝒖𝒏 = 𝟑𝒏 = 𝟖 𝟑𝒏−𝟐 ,
𝟗 ?
(b) the term-to-term formula, stating any
initial terms required.
𝒖𝒏 = 𝟑𝒖𝒏−𝟏 , 𝒖𝟏 = 𝟖 ?
e.g. For 3, 5, 7, 9, … −1, +1, −1, +1, −1 …
(a) 𝑢𝑛 = 2𝑛 + 1, 6
(b) 𝑢𝑛 = 2𝑢𝑛−1 , 𝑢1 = 3
𝒖𝒏 = −𝟏 𝒏 ,
𝒖𝒏 = −𝒖𝒏−𝟏 , 𝒖𝟏 = −𝟏
?
?
1 0, 1, 2, 3, 4 … 0.5, 0.25, 0.125, 0.0625 …
7
𝒖𝒏 = 𝒏 − 𝟏, ? 𝟏 𝒏
𝒖𝒏 = 𝒖𝒏−𝟏 + 𝟏, 𝒖?𝟏 = 𝟎 𝒖𝒏 =
𝟐
𝒖𝒏−𝟏
?
= 𝟐−𝒏 ,
𝒖𝒏 = , 𝒖𝟏 = 𝟎. 𝟓
𝟐 ?
2 6, 11, 16, 21, … A sequence has the term-to-term formula
𝒖𝒏 = 𝟓𝒏 + 𝟏, ? 8
𝑢𝑛 = 2𝑢𝑛−1 + 1 where 𝑢1 = 1. Find the
𝒖𝒏 = 𝒖𝒏−𝟏 + 𝟓, 𝒖𝟏 = 𝟔
? position-to-term formula.
𝒖𝒏 = 𝟐 𝒏 − 𝟏 ?
3 4, 16, 64, 256 …
𝒖𝒏 = 𝟒 𝒏 , ? N1
1, −2, 3, −4, 5, −6, …
𝒖𝒏 = 𝟒𝒖𝒏−𝟏 , 𝒖𝟏 =?𝟒 𝒖𝒏 = 𝒏 −𝟏 𝒏−𝟏 , ?
(Term-to-term formula not required)

## 4 3, 6, 12, 24, … 0, 50, 75, 87.5, 93.75 …

𝟑
𝒖𝒏 = 𝟐 × 𝟐𝒏 = 𝟑?𝟐𝒏−𝟏 , N2
𝒖
?
𝒖𝒏 = 𝟏𝟎𝟎 − 𝟏𝟎𝟎 𝟐𝟏−𝒏 ,
𝒖𝒏 = 𝐧−𝟏 + 𝟓𝟎, 𝒖𝟏 = 𝟎
𝒖𝒏 = 𝟐𝒖𝒏−𝟏 , 𝒖𝟏 ?
=𝟑 𝟐 ?
Second Difference
What do you notice about the difference?

## 3, 8, 15, 24, 35, …

Working out 𝑢𝑛

𝑛 1 2 3 4 5 STEP 1: Write
out 𝑛 and 𝑢𝑛

## 𝑢𝑛 3 8 15 24 35 STEP 2: Work out

second difference.
+5 +7 +9

## +2 +2 STEP 3: Halve this

to find coefficient
2 of 𝑛2 term.
1𝑛 1 4 9 16 25
STEP 4: Work out
Adjust +2 +4 +6 +8 +10 what we need to add
to get from this to
correct term. Work
2 out its formula.
𝑢𝑛 = 𝑛 + 2𝑛
More Examples
2
3, 9, 19, 33, 51, … 𝑢𝑛 = 2𝑛 + 1?

? −1

? +3
Exercise 2

## 1 3, 7, 13, 21, 31, … 𝑢𝑛 = 𝑛2 + 𝑛?+ 1

2 5, 13, 25, 41, 61, 85, … 𝑢𝑛 = 2𝑛2 + 2𝑛
? +1
3 2, 3, 6, 11, 18, … 𝑢𝑛 = 𝑛2 − 2𝑛
? +3
4 5, 17, 35, 59, 89, 125, … 𝑢𝑛 = 3𝑛2 + 3𝑛
? −1
1 2
5 1.5, 4, 7.5, 12, 17.5, 24, … 𝑢𝑛 = 𝑛 + ?𝑛
2
6 1, 10, 23, 40, 61, 86, … 𝑢𝑛 = 2𝑛2 + 3𝑛
? −4
7 4, 5, 4, 1, −4, −11, … 𝑢𝑛 = −𝑛2 + ?4𝑛 + 1
1 2
8 3.5, 7, 9.5, 11, 11.5, 11, … 𝑢𝑛 = 𝑛 + ?5𝑛 − 1
2
Levelled Sequences Activity

## If correct, you can proceed to Level 2 and so on.

Sequence Proofs
In a sequence each number is the sum of the two previous terms.
If the 3rd term is 5 and the 5th term is 6, what is the 6th term?
(Hint: we don’t know the first two terms, so what should we do?)

## Let 𝒂 be the first term and 𝒃 the second.

Then the terms are:
𝒂, 𝒃, 𝒂 + 𝒃, 𝒂 + 𝟐𝒃, 𝟐𝒂 + 𝟑𝒃, 𝟑𝒂 + 𝟓𝒃
Thus:
𝒂 + 𝒃 =?𝟓
𝟐𝒂 + 𝟑𝒃 = 𝟔
∴ 𝒂 = 𝟗, 𝒃 = −𝟒
The 5th term is then 𝟑 × 𝟗 + 𝟓 × −𝟒 = 𝟕.

## The key point therefore is that we have generically

represented unknown terms (usually the initial terms which
later terms depend on) using variables, in order to reason
Each term in a sequence is formed by taking the previous term and subtracting the
term before that.
The fourth term of the sequence is 10 and the sum of the first four terms is 20.
Determine the 5th term.

## First five terms:

𝒂, 𝒃, 𝒃 − 𝒂, −𝒂, −𝒃
Therefore:
−𝒂 = 𝟏𝟎
𝒂 + 𝒃 + 𝒃 − 𝒂 − 𝒂 = ?−𝒂 + 𝟐𝒃 = 𝟐𝟎
∴𝒃=𝟓
The 5th term is therefore:
−𝒃 = −𝟓
Exercise 4 (See printed sheet)

## Let the first two terms of a sequence be 𝑎 and

1 3 [IMC 2015 Q14] In a sequence, each term
𝑏. Each term thereafter is the sum of the
after the first two terms is the mean of all
previous 2 terms.
the terms which come before that term.
a) Find an expression for the 5th term and
The first term is 8 and the tenth term is 26.
6th term, each in terms of 𝑎 and 𝑏.
What is the second term?
b) If the 5th term is 5 and the 6th term 7,
A 17 B 18 C 44
solve your equations simultaneously to
D 52 E 68
determine 𝑎 and 𝑏.
(a) 𝟐𝒂 + 𝟑𝒃 and 𝟑𝒂 + 𝟓𝒃 (b) 𝒂 = 𝟒, 𝒃 = −𝟏
?
Solution: C
?
4 [IMC 2012 Q17] The first term of a
2 [IMC 2002 Q11] The Fibonacci sequence 1, 1,
sequence of positive integers is 6. The other
2, 3, 5, 8, 13, … begins with two 1s, and each
terms in the sequence follow these rules:
later number in the sequence is the sum of the
* if a term is even then divide it by 2 to
previous two numbers. Other Fibonacci-like
obtain the next term;
sequences can be constructed by starting with
* if a term is odd then multiply it by 5 and
any two numbers 𝑎 and 𝑏 (not necessarily 1
subtract 1 to obtain the next term.
and 1) and using the same rule for creating the
For which values of 𝑛 is the 𝑛th term equal
other numbers in the sequence. What is the
to 𝑛?
first term of the Fibonacci-like sequence
A 10 only B 13 only C 16 only
whose second term is 4 and whose fifth term
D 10 and 13 only E 13 and 16 only
is 22?
Solution: E
A 2 B 3 C 4 ?
D 5 E 6
Solution: D
?
Exercise 4 (See printed sheet)

5 [Cayley 2013 Q3] Consider sequences of 7 [Hamilton 2004 Q4] The first two terms of a
positive integers for which both the following sequence are the numbers 1, 2. From then on,
conditions are true: each term is obtained by adding 1 to the
(a) each term after the second term is the sum previous term and then dividing by the term
of the two preceding terms; before that. Thus the third term is obtained by
(b) the eighth term is 260. adding 1 to the second term and then dividing
How many such sequences are there? by the first term.
Two. First two terms could be 13, 12 or 26, 4. (a) Write down the first five terms.
? (b) Calculate the sixtieth term.
6 [Cayley 2004 Q4] The first two terms of a (c) What happens if the other non-zero
sequence are the numbers 1, 2. From then on, numbers are chosen for the first two terms, but
each term is obtained by dividing the previous the rule for calculating the next term remains
term by the term before that. Thus the third the same?
term is obtained by dividing the second term, 2, (a) 1, 2, 3, 2, 1 (b) 1 (c) Let first two
by the first term, 1. terms be 𝒂, 𝒃. Then sequence is
(a) Write down the first five terms. 𝒃+𝟏 𝒃+𝟏+𝒂 𝒂+𝟏

## (b) Calculate the fiftieth term.

𝒂, 𝒃,
𝒂
,
𝒂𝒃
,
𝒃 ?
, 𝒂, 𝒃. Since each term is
based only on previous two terms, we have
(c) What happens if other non-zero numbers
proven the sequence repeats every five terms.
are chosen for the first two terms, but the rule
for calculating the next term remains the same?
𝟏
(a) 1, 2, 2, 1, (b) 2
𝟐
(c) If first two terms 𝒂, 𝒃 then sequence is
𝒃 𝟏 𝟏 𝒂 ?
𝒂, 𝒃, , , , , 𝒂, 𝒃, …which repeats every 6
𝒂 𝒂 𝒃 𝒃
terms.
Exercise 4 (See printed sheet)

8 [Maclaurin 2007 Q1] The first term c of a 9 [Hamilton 2010 Q3] The first and second
sequence is not equal to 1. Each time after terms of a sequence are added to make the
the first is equal to “(3 more than the third term. Adjacent odd-numbered terms are
previous term) divided by (1 less than the added to make the next even-numbered term,
previous term)”. for example,
(a) What values of c make the sequence recur First term + third term = fourth term
forever, in the form c, c, c, c, c, …? And third term + fifth term = sixth term
(b) Is it possible for any term of the sequence Likewise, adjacent even-numbered terms are
to be equal to 1? added to make the next odd-numbered term,
for example,
Solution: Second term + fourth term = fifth term
(a) 𝒄 = −𝟏 or 𝒄 = 𝟑 Given that the seventh term equals the eighth
(b)
𝒙+𝟑 ?
= 𝒙. Then 𝒙 + 𝟑 = 𝒙 − 𝟏 which
term, what is the value of the sixth term?
𝒙−𝟏 Solution: 0
clearly has no solutions. ?
10 [Kangaroo Grey 2013 Q22] The first five terms
of a sequence are 1, -1, -1, 1, -1. After the fifth
term, every term is equal to the product of
the two preceding terms. For example, the
sixth term is equal to the product of the
fourth term and the fifth term. What is the
sum of the first 2013 terms of the sequence?
A -1006 B -671 C 0
D 671 E 1007
Solution: A
Exercise 4 (See printed sheet)

## 11 [Kangaroo 2002 Q25] The sequence

1, 𝑥, … , 1000 is the longest sequence of
positive integers, with first term 1 and last
term 1000, having the property that each
term after 𝑥 is the sum of all the previous
terms. What is the value of 𝑥?
A 124 B 125 C 249
D 224 E 120
Solution: B ?

## 12 [Kangaroo Pink 2004 Q25] Owl wrote all

the whole numbers from 1 to 10 000 on a
blackboard. After that he erased the
numbers which are neither divisible by 5
nor by 11. What was the 2004th term of
the remaining sequence?
A 1000 B 5000 C 6545
D 7348 E 10 000
Solution: D
?
Year 9 Possible Extension Lesson
Dr J Frost (jfrost@tiffin.kingston.sch.uk)
The general form of...

## A linear (“first difference”) sequence:

𝑢𝑛 = 𝑎𝑛 +?𝑏
A quadratic (“second difference”) sequence:

𝑢𝑛 = 𝑎𝑛2 + 𝑏𝑛
? +𝑐
Why does the first difference...
...become the number on front of the n?

## Current Term Next Term

Position 𝑛 𝑛 +? 1
Term 𝑎𝑛 + 𝑏 𝑎𝑛 + ?𝑎 + 𝑏

a?
Why does the second difference...
...get halved then put on front of n2?

## Current Term Next Term Term after that

Position 𝑛 ? 1
𝑛+ 𝑛 +? 2
Term 𝑎𝑛2 + 𝑏𝑛 + 𝑐 𝑎𝑛2 + 2𝑎𝑛 𝑎𝑛2 + 4𝑎𝑛 + 𝑏𝑛
? + 𝑏𝑛 ? +𝑐
+ 4𝑎 + 2𝑏
+𝑎+𝑏+𝑐

## 2𝑎𝑛 +?𝑎 + 𝑏 2𝑎𝑛 + ?3𝑎 + 𝑏

2𝑎
?
Since the second difference is 2𝑎 and the coefficient of 𝑛2 is 𝑎, we can
see halving the second difference gives us the coefficient of 𝑛2 .
Finding a formula using simultaneous equations
You’re given the first three terms of a quadratic (second difference) sequence:
𝒖𝟏 = 𝟑, 𝒖𝟐 = 𝟕, 𝒖𝟑 = 𝟏𝟓
We know that we can use:
𝒖𝒏 = 𝒂𝒏𝟐 + 𝒃𝒏 + 𝒄

## What equations can we form?

𝒂+𝒃+𝒄 =𝟑 (𝟏)
𝟒𝒂 + 𝟐𝒃 + 𝒄 =?𝟕 (𝟐)
𝟗𝒂 + 𝟑𝒃 + 𝒄 = 𝟏𝟓 (𝟑)
Solve by elimination:

2 − 1 : 3𝑎 + 𝑏 = 4
3 − 1 : 8𝑎 + 2𝑏 = 12
?
𝑎 = 2, 𝑏 = −2, 𝑐 = 3
𝑢𝑛 = 2𝑛2 − 2𝑛 + 3

1, 4, 13, ...
2
𝑢𝑛 = 3𝑛 − 6𝑛 ? +4

## Oxford Maths Admissions Exam - 2009

x4 = 10, x5 ?
= 15

? C = 0.5
A = 0, B = 0.5,

n = 40 ?
Further Exercises
Solve the following by forming simultaneous equations.
1 Given that 𝑢1 = 2, 𝑢2 = 7, 𝑢3 = 14 and that the formula for the sequence is
𝑢𝑛 = 𝑎𝑛2 + 𝑏𝑛 + 𝑐, form simultaneous equations, and hence determine 𝑎, 𝑏 and 𝑐.
𝒂 = 𝟏, 𝒃 = 𝟐, 𝒄 = −𝟏
?
2 A line with equation 𝑦 = 𝑎𝑥 2 + 𝑏𝑥 + 𝑐 goes through the points 1,0 , 2, 7 , 3, 18 .
Determine 𝑎, 𝑏 and 𝑐.
?
𝒂 = 𝟐, 𝒃 = 𝟏, 𝒄 = −𝟑

A line with equation 𝑦 = 𝑎𝑥 2 + 𝑏𝑥 + 𝑐 goes through the points 2,10 , (4,46) and 5,73 .
3
Determine 𝑎, 𝑏 and 𝑐.
?
𝒂 = 𝟑, 𝒃 = 𝟎, 𝒄 = −𝟐
2
A line has equation 𝑦 = 𝑥𝑎 𝑥 , where 𝑎 is a constant. It passes through the point 2, 162 .
4
Determine the 𝑦-value when 𝑥 = 3.
?
𝒚 = 𝟑𝟏𝟎 = 𝟓𝟗𝟎𝟒𝟗
By forming suitable simultaneous equations (or otherwise), determine the formula for the nth
N
term of the sequence…
1, 1, 1, 2, 5, 11, 21, … NN Prove that the coefficient of the 𝑛 3
term in a
𝟏 𝟏𝟏 1
𝒖𝒏 = 𝒏𝟑 − 𝒏𝟐 + 𝒏 cubic sequence is of the third difference.
𝟔 ? 𝟔
6
More generally, if the 𝑘 th difference was
constant, what do you think the coefficient of
the 𝑛𝑘 term will be? (NNN Prove it.)